Aspects of the genetic and botanical status of neotropical azolla species - Zimmerman, William J.; Watanabe, Iwao; Ventura, Teresita; Payawal, Pacifico; Lumpkin, Thomas A. (Wiley, 1991)
Variation among neotropical and other species of the aquatic fern Azolla Lam, was examined using molecular and physiological parameters. The three neotropical species of Section Azolla, A. caroliniana Willd., A. mexicana Presl, and A. microphylla Kaulf., were very similar in their DNA fingerprints from hybridizations to heterologous and random homologous gene probes. These Azolla were also not separable by their symptomatic responses to phosphorus deficiency, although subgroups were observed that correlated to the +/− responses of cyanobionts to the monoclonal antibody McAb‐C16. The strong affinity among these taxa was also demonstrated in breeding trials between A. mexicana‐caroliniana and A. microphylla which yielded the first fertile Azolla hybrids, unlike previous Section Azolla crosses between A. filiculoides and A. mexicana or A. microphylla. Cumulative evidence indicates a need to reclassify Azolla of the New World.